Challenges of management- district magistrates in India - Goel, Anurag; Richard, Paton
According to the author the job of a district magistrate is a critical link between the Government and the millions of people who live in districts throughout India. The Indian People in these positions can make a major contribution to successful administration in this country, because this job of district magistrate is so important that it is essential to be done well. In foreign countries like the United Kingdom, Canada and the United States, these studies conducted and their roles and key elements revealed that one could learn a great deal about the main elements that enable managers and leaders successfully manage companies or government departments by studying how managers to their jobs. This study focu
Keywords: Management; District Magistrate; Accountability; District Administration - India